Gout and pseudo-gout-related crystals promote GLUT1-mediated glycolysis that governs NLRP3 and interleukin-1β activation on macrophages. Issue 11 (22nd July 2020) - Renaudin, Felix; Orliaguet, Lucie; Castelli, Florence; Fenaille, François; Prignon, Aurelie; Alzaid, Fawaz; Combes, Christele; Delvaux, Aurélie; Adimy, Yasmina; Cohen-Solal, Martine; Richette, Pascal; Bardin, Thomas; et al.
Abstract : Objective: Macrophage activation by monosodium urate (MSU) and calcium pyrophosphate (CPP) crystals mediates an interleukin (IL)-1β-dependent inflammation during gout and pseudo-gout flare, respectively. Since metabolic reprogramming of macrophages goes along with inflammatory responses dependently on stimuli and tissue environment, we aimed to decipher the role of glycolysis and oxidative phosphorylation in the IL-1β-induced microcrystal response. Methods: Briefly, an in vitro study (metabolomics and real-time extracellular flux analysis) on MSU and CPP crystal-stimulated macrophages was performed to demonstrate the metabolic phenotype of macrophages. Then, the role of aerobic glycolysis in IL-1β production was evaluated, as well in vitro as in vivo using 18 F-fluorodeoxyglucose positron emission tomography imaging and glucose uptake assay, and molecular approach of glucose transporter 1 (GLUT1) inhibition. Results: We observed that MSU and CPP crystals led to a metabolic rewiring toward the aerobic glycolysis pathway explained by an increase in GLUT1 plasma membrane expression and glucose uptake on macrophages. Also, neutrophils isolated from human synovial fluid during gout flare expressed GLUT1 at their plasma membrane more frequently than neutrophils isolated from bloodstream. Both glucose deprivation and treatment with either 2-deoxyglucose or GLUT1 inhibitor suppressed crystal-induced NLRP3 activation and IL-1β production, and microcrystal inflammation in vivo. Conclusion: In conclusion, we demonstrated that GLUT1-mediated glucose uptake is instrumental during the inflammatory IL-1β response induced by MSU and CPP crystals. These findings open new therapeutic paths to modulate crystal-related inflammation.